Gambaran Karakteristik Pasien Dispepsia di Rumah Sakit - Reci Anglena; Maulani Maulani; Dasuki Dasuki (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Dyspepsia is a disease of the digestive tract that is not contagious but is common among people in the world. Dyspepsia can be experienced by various age ranges, gender. According to research, the risk factor for organic dyspepsia is age > 50 years. This is thought to be related to the increasing prevalence of chronic diseases in old age. Dyspepsia has an impact on quality of life because the natural course of dyspepsia is chronic and often recurs. This research is a quantitative research using a descriptive analytic research design. The sample in this study were dyspepsia patients at Nurdin Hamzah General Hospital, East Tanjung Jabung Regency, totaling 80 people. The sampling technique used in this research is purposive sampling technique. This research was conducted at the Nurdin Hamzah General Hospital, East Tanjung Jabung Regency, in 26 June – 04 July 2023, then the data will be obtained by looking at the medical records of dyspepsia patients at the Nurdin Hamzah General Hospital, East Tanjung Jabung Regency. Data analysis was performed univariately. Based on the results of the study, it was found that patients aged > 65 years (elderly) were 20 respondents (25%) with dyspepsia, some of the dyspepsia patients were female, namely 55 respondents (68.8%), with working status, namely 44 respondents (55.0%) ), patients had a history of co-morbidities, namely 47 respondents (58.8%) and most dyspepsia patients had a history of drug use, namely 43 respondents (53.8%). It is recommended as input to the hospital to find out the problem about the description of the characteristics of dyspepsia patients